Japanese journal of religious studies : JJRS (Nanzan Shūkyō Bunka Kenkyūjo [Tb1], 1974)
"A peer-reviewed journal specializing in the publication of research on the study of Japanese religions. The journal aims for a multidisciplinary approach to the study of religion in Japan, and submissions are welcomed from scholars in all fields of the humanities and social sciences"